Trends in Socioeconomic Inequalities in Hypertension in Ontario, Canada, 2000-2012 - Simran Shokar; Laura Rosella; Peter Smith; Hong Chen; Heather ChenManson; Jack Tu; Brendan Smith (International Journal of Population Data Science, 2018)
Introduction Hypertension is leading risk factor for cardiovascular disease and mortality. Low socioeconomic position (e.g., income or high material deprivation) is an important risk factor for hypertension. However, there is limited evidence monitoring the extent to which socioeconomic inequalities in hypertension exist and are changing over time in Ontario.